Maturation of a Key Resource – The Germanium-68/Gallium-68 Generator: Development and New Insights - Roesch, F. (Current Radiopharmaceuticals, 2012)
68Ge/68Ga radionuclide generators have been investigated for almost fifty years, since the cyclotronindependent availability of positron emitting 68Ga via the 68Ge/68Ga system had always attracted researches working in basic nuclear chemistry as well as radiopharmaceutical chemistry. However, it took decades and generations of research (and researchers) to finally reach a level of 68Ge/68Ga radionuclide generator designs adequate to the modern requirements of radiometal labelling chemistry. Nevertheless, most of the existing commercial generator systems address aspects of 68Ge breakthrough and safe synthesis of 68Ga radiopharmaceuticals by adopting eluate post-processing technologies. Among the strategies to purify 68Ga eluates, the cation exchange based version is relevant in terms of purification efficiency. In addition, it offers more options towards further developments of 68Ga radiopharmaceuticals. Today, one may expect that the 68Ge/68Ga radionuclide generator systems could contribute to the clinical impact of nuclear medicine diagnoses for PET similar to the established 99Mo/99mTc generator system for SPECT. The exciting perspective for the 68Ge/68Ga radionuclide generator system, in turn, asks for systematic chemical, radiochemical, technological and radiopharmaceutical efforts, to guarantee reliable, highly-efficient and medically approved 68Ge/68Ga generator systems.
Keywords: Cation Exchange Resin